Use of computed tomography to determine the risk of patellar dislocation in 921 patients with patellar instability - Schueda MA; Astur DC; Bier RS; Bier DS; Astur N; Cohen M (Open Access Journal of Sports Medicine, 2015)
Marco Antonio Schueda,1 Diego Costa Astur,2 Rodrigo Schueda Bier,3 Debora Schueda Bier,4 Nelson Astur,5 Moisés Cohen2 1Serviço de Pós Graduação em Cirurgia do Joelho e Artroscopia do IOT e Traumasports de Joinville, Joinville, Santa Catarina, 2Departamento de Ortopedia e Traumatologia da Escola Paulista de Medicina, São Paulo, 3Serviço de Cirurgia do Joelho e Artroscopia do IOT e Traumasports de Joinville, Joinville, Santa Catarina, 4Pontifícea Universidade Católica, Curitiba, 5Faculdade de Ciencias Médicas da Santa Casa de Misericórdia de São Paulo, São Paulo, Brazil Abstract: The purpose of this research was to identify reliable tomographic measurements that can detect patellofemoral abnormality and allow quantification of the risk of patellar dislocation in patients with potential patellar instability. A cross-sectional study in 921 patients with anterior pain or knee instability of at least 6 months' duration was conducted from July 2001 to December 2009. All subjects were clinically evaluated and underwent radiography and computed tomography of their knees. According to their degree of dislocating patellar dysplasia, the subjects were classified into groups for statistical comparison. There was a statistically significant difference in all measurements when the groups were compared, except for external tibial torsion angle. The most sensitive and specific measurements for determining patellar instability were the trochlear groove angle, tibial tubercle-trochlear groove distance, average patellar tilt, and average patellar height. Patients with potential patellar instability, increased tibial tubercle-trochlear groove distance, and patellar height, tilt, and deviation measurements had a greater risk for patellar dislocation. The clinical relevance of this study is to determine measurements that are able to tell us about patellar dislocation risk. Keywords: patellofemoral instability, knee, patellofemoral syndrome